Client importance and audit quality - Nunes, M.; Pais, C. (20th EUFIN - The Conference of Accounting in Europe, 2025)
This study analyzes the importance of the client in audit quality and whether this relationship is influenced by the change in the audit report, imposed by the European Union, which occurred from 2016. The sample consists of Spanish listed companies for the period from 2010 to 2022. The importance of the client is measured by audit/non-audit fees at the audit partner, audit office and audit firm level. While audit quality is measured through discretionary accruals and modified opinion, and as an additional test, through the number of key audit matters. It is concluded that the importance of the client increases the quality (measured by discretionary accruals) of the audit at the audit office level, but that it decreases it at the audit firm level, and no conclusion can be drawn in the case of the audit partner. When audit quality is measured through the modified opinion, no conclusion can be drawn regarding its relationship with the importance of the client. Regarding the influence of the audit report on the relations between the importance of the client and audit quality, it is concluded that this has decreased at the office audit level.